æ¼¢åã®å¦ã³æ¹ - Diner, Lispridona (Language Circle: Journal of Language and Literature, 2013)
The objectives of teaching kanji characters are among other things that while reading them the learners are able to understand their meaning, to know their forms and how to read them. In speed reading, thorough understanding of such writing system is obligatory. However, the students of Japanese Language Education still face difficulties in understanding such system. What they obtain is merely memorization of the characters; they are unable to read particular characters which are put side by side with other similar characters. Besides, they are also confused when learning the large number of the characters. In order to overcome the difficulties, the writer has provided a correct way of learning how to read such writing system through the following procedures: pay attention to the form of the characters (radical/bushu), pay attention to their sounds (ompu), read the characters, understand their meanings (imi) through learning them at word level (goi reberu).Â æ¼¢åã®å¦ç¿ç®æ¨ã¯ãèªãã¨ãã«æ¼¢åãçè§£ã§ããããã«ãªããã¨ã§ãæ¸ãã¨ãã«æ¼¢åãä½¿ãããã¨ã«å¤§å¥ããããèªãã¨ãã«æ¼¢åãçè§£ã§ããããã«ã¯ãæ¼¢åã®æå³ãç¥ã£ã¦ãããã¨ãæ¼¢åã®èªã¿æ¹ãç¥ã£ã¦ãããã¨ãæ¼¢åã®å½¢ãèªèã§ãããã¨ãæ¼¢åèªå½ã®æå³ãããããæãèªãéã«ããç¨åº¦ã®é ãã§çè§£ãããã¨ãå¿è¦ã¨ãªããã¹ãã©ã³å½ç«å¤§å¦ã®æ¥æ¬èªæè²ããã°ã©ã ã«ããã¦æ¼¢åå¦ç¿èã®å ´åãåææ®µéã§ã¯æ¼¢åã®å½¢ãè¦åãããã¨ãå°é£ãªãã¨ãå¤ããããã§ãã¾ããåæ¼¢åã¬ãã«ã§æ¼¢åã®å½¢ãæç¤ºããæå³ãé³ã¨å¯¾å¿ä»ãããããªæ´»åãè¡ããã¨ãå¤ããã¾ããæ¼¢åãåæºãã¤ã¡ã¼ã¸ã¨ããã³ã¤ãããã¹ããªã¼ãä½ã£ãããã¦æå³ãè¨æ¶ãããªã©ã®æ¹æ³ãã¨ããããæ¼¢åã®å¦ç¿å°é£ãåæããããããæ¼¢åã®å½¢ã«æ³¨ç®ããæ¹æ³ãæ¼¢åã®èªã¿ã«æ³¨ç®ããæ¹æ³ãæ¼¢åã®æå³ã«æ³¨ç®ããæ¹æ³ãåèªã¬ãã«æ¹æ³ãã®æ¹æ³ãä½¿ãã®ãããã¨æãã